2020
DOI: 10.1002/nem.2099
|View full text |Cite
|
Sign up to set email alerts
|

FastFabric: Scaling hyperledger fabric to 20 000 transactions per second

Abstract: Summary Blockchain technologies are expected to make a significant impact on a variety of industries. However, one issue holding them back is their limited transaction throughput, especially compared to established solutions such as distributed database systems. In this paper, we rearchitect a modern permissioned blockchain system, Hyperledger Fabric, to increase transaction throughput from 3000 to 20 000 transactions per second. We focus on performance bottlenecks beyond the consensus mechanism, and we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(52 citation statements)
references
References 12 publications
0
38
0
1
Order By: Relevance
“…Therefore, a design goal of QiOi is to control the scheduling delay via CPU allocation of Fabric components. We focus on the orderers and the peers because their impacts have been known on determining Fabric performance [16,[36][37][38].…”
Section: Performance Interference Analysismentioning
confidence: 99%
“…Therefore, a design goal of QiOi is to control the scheduling delay via CPU allocation of Fabric components. We focus on the orderers and the peers because their impacts have been known on determining Fabric performance [16,[36][37][38].…”
Section: Performance Interference Analysismentioning
confidence: 99%
“…The public blockchain application to the PKI context is presented in [12]- [16]. The scaling up Hyperledger Fabric blockchain network is explained in [18].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the REST API has some more latency than protocols such as gRPC (Google Remote Procedure Calls) and TCP sockets. Since the limitation of scaling is entirely dependent on the blockchain platform, it can be eliminated by either deploying more miner nodes or using a plug-and-play scalability improvement technique such as [18].…”
Section: Limitations Of the Implementationmentioning
confidence: 99%
“…Hyperledger fabric has a concurrency controller that help increase throughput when processing transactions. A recent research [46] has also demonstrated the re-engineering of a hyperledger fabric to increase transaction throughput from 300 to nearly 20,000 transactions per second. Similar work has also been conducted in [47] and [48] to attest the better performance of the permissioned blockchain based on the hyperledger fabric than that of the permission less blockchain.…”
Section: ) Performancementioning
confidence: 99%